2011
DOI: 10.1248/bpb.34.1330
|View full text |Cite
|
Sign up to set email alerts
|

Allergy-Preventive Effects of Chlorogenic Acid and Iridoid Derivatives from Flower Buds of Lonicera japonica

Abstract: Flower buds of Lonicera japonica THUNB. (Caprifoliaceae), one of the most common traditional Chinese medicines, are used to treat various diseases including arthritis, diabetes mellitus, fever, infections, sores and swelling. 1)Pharmacological studies have indicated that the extract of these flower buds have a broad spectrum of biological activities, including antibacterial, anti-inflammatory, antioxidant, antipyretic, antiviral and hepato-protective effects.1,2) A number of chemical constituents including fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
0
29
1
Order By: Relevance
“…Therefore, the need for alternative, more effective, and widely applicable antidotes for APinduced liver injury is warranted. Chlorogenic acid (CGA) is the major active ingredient found in many traditional Chinese medicines such as Folium mori (Hunyadi et al, 2012) and Flos Lonicerae japonicae (Oku et al, 2011), and it is also abundant in some fruits, dietary vegetables (Kasai et al, 2000;Gavrilova et al, 2011), and daily beverages like coffee (del Rio et al, 2010). CGA has been reported to possess anti-bacterial, antioxidant, and anti-carcinogenic properties (Kono et al, 1997;dos Santos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the need for alternative, more effective, and widely applicable antidotes for APinduced liver injury is warranted. Chlorogenic acid (CGA) is the major active ingredient found in many traditional Chinese medicines such as Folium mori (Hunyadi et al, 2012) and Flos Lonicerae japonicae (Oku et al, 2011), and it is also abundant in some fruits, dietary vegetables (Kasai et al, 2000;Gavrilova et al, 2011), and daily beverages like coffee (del Rio et al, 2010). CGA has been reported to possess anti-bacterial, antioxidant, and anti-carcinogenic properties (Kono et al, 1997;dos Santos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that the decrease in peripheral blood flow was involved in the paclitaxelinduced mechanical allodynia. 11) Since aucubin does not affect decrease of peripheral blood flow, 12) it is suggested that it may inhibit the exacerbation of paclitaxel-induced mechanical allodynia through mechanisms other than the control of peripheral blood flow.…”
Section: Abstract Paclitaxel; Mechanical Allodynia; Aucubin; Firing;mentioning
confidence: 99%
“…This suggested that the decrease in peripheral blood flow was involved in the paclitaxelinduced mechanical allodynia. 11) Since aucubin does not affect decrease of peripheral blood flow, 12) it is suggested that it may inhibit the exacerbation of paclitaxel-induced mechanical allodynia through mechanisms other than the control of peripheral blood flow.Peripheral demyelination contributes majorly to plasticity in neuropathic pain.13) However, paclitaxel promotes demyelination of the sciatic nerve.14,15) Myelin sheaths formed by Schwann cells are damaged by paclitaxel 15) through the induction of endoplasmic reticulum (ER) stress. 16,17) Therefore, the aim of this study was to investigate whether aucubin alleviates paclitaxel-induced nerve activity and ER stress in mice.…”
mentioning
confidence: 99%
“…Chlorogenic acid and luteoloside, officially used as the indicator compound to characterize the quality of this herb and its related preparations, were shown to have beneficial effects in the aspects of anti-oxidation and antitumor [1,13]. Moreover, chlorogenic acid showed the antibacterial, antiviral, anti-inflammatory, hypoglycemic activities, and allergy-preventive properties [1,14]. Meanwhile, luteolin, another major flavonoid in Jinyinhua, and volatile oil also showed significant anti-inflammatory activity.…”
Section: Pharmacological Studiesmentioning
confidence: 99%